Combined chemical transformation and biological transformation of artemisinin: A facile approach to diverse artemisinin derivatives - Gao, Xinna; Bai, Yue; Sun, Peng; Gao, Huimin; Yang, Lan; Zhang, Dong; Zhao, Yifan; Ma, Yue (Frontiers in Chemistry, 2023)
Introduction: Artemisinin (1) is a milestone compound in malaria treatment, and it exhibits a broad scope of bioactivities. Herein, sequential chemo-reduction and biotransformation of artemisinin were undertaken to obtain a series of artemisinin derivatives. Methods: First, 10-deoxyartemisinin (2) and 9-ene-10-deoxyartemisinin (3) were synthesized after simple handling with boron trifluoride/diethyl ether and sodium borohydride. Then, biotransformation of 10-deoxyartemisinin was conducted with Cunninghamella echinulata CGMCC 3.4879 and Cunninghamella elegans CGMCC 3.4832, and the transformed products were separated and identified. The antimalarial activity of these products was tested in vitro against Plasmodium falciparum 3D7. Results: Fifteen metabolites (4–18), including seven novel compounds, were isolated and identified after cultivation. Compounds 2, 3, 13, 15, 16, and 18 displayed moderate-to-good antimalarial activity, with a half-maximal inhibitory concentration ranging from 6 to 223 nM. Discussion: This work explored the combination of chemical and biological transformation to develop a co-environmental, efficient, and cost-efficiency synthetic methodology and applied it to synthesize novel derivatives of artemisinin. The association of the two strategies will hopefully provide an abundant source for the development of novel drugs with bioactivities.